CHARACTERISTICS OF BOOKKEEPING BEFORE PACIOLO. - De Roover, Raymond (The Accounting Review, 1938)
Abstract It is now generally accepted that double-entry bookkeeping is by no means the invention of one man nor the product of a single generation, but that it is the result of a long evolution. Even today, it progresses under the spur of actual needs, and its development is the result of a persistent effort to adapt the accounting methods to the growing requirements of business enterprise. Its evolution in the past has been dominated by the same commanding necessity of adaptation. There is, however, still one dark spot in the history of accounting. Although it can be perceived fairly well how the double-entry system developed, once the basic principle of duality and equilibrium was laid down, it is hard to understand how it came into being. As a matter of fact, the specialists of the history of bookkeeping have all tried to solve the problem and to offer some satisfactory explanation. Owing to a lack of source material, these solutions, however, are based mainly on conjectural reasoning rather than on factual evidence. Three factors seem to have contributed to the development of accounting: credit, partnership, and agency.